Additive manufacturing of a functionally graded material from Ti-6Al-4V to Invar: Experimental characterization and thermodynamic calculations. (1st April 2017) - Bobbio, Lourdes D.; Otis, Richard A.; Borgonia, John Paul; Dillon, R. Peter; Shapiro, Andrew A.; Liu, Zi-Kui; Beese, Allison M.
Abstract: In functionally graded materials (FGMs), the elemental composition, or structure, within a component varies gradually as a function of position, allowing for the gradual transition from one alloy to another, and the local tailoring of properties. One method for fabricating FGMs with varying elemental composition is through layer-by-layer directed energy deposition additive manufacturing. This work combines experimental characterization and computational analysis to investigate a material graded from Ti-6Al-4V to Invar 36 (64 wt% Fe, 36 wt% Ni). The microstructure, composition, phases, and microhardness were determined as a function of position within the FGM. During the fabrication process, detrimental phases associated with the compositional blending of the Ti-6Al-4V and Invar formed, leading to cracking in the final deposited part. Intermetallic phases (FeTi, Fe2 Ti, Ni3 Ti, and NiTi2 ) were experimentally identified to occur throughout the gradient region, and were considered as the reason that the FGM cracked during fabrication. CALPHAD (CALculation of PHase Diagrams) thermodynamic calculations were used concurrently to predict phases that would form during the manufacturing process and were compared to the experimental results. The experimental-computational approach described herein for characterizing FGMs can be used to improve the understanding and design of other FGMs. Graphical abstract: